Topologically influenced terahertz emission in Co2MnGa with a large anomalous Hall effect - Ruma Mandal; Ren Momma; Kazuaki Ishibashi; Satoshi Iihama; Kazuya Suzuki; Shigemi Mizukami (NPG Asia Materials)
Abstract The terahertz (THz) spectral zone is one of the most exciting but least explored domains of the electromagnetic spectrum. To extend the applicability of THz waves, the present objective is to develop an efficient, compact, durable, and low-cost THz emitter source. A spintronic THz emitter consisting of a ferromagnetic/nonmagnetic bilayer heterostructure is a promising innovation that can provide an alternative solution/replacement for conventional THz emitters. To further develop these spin-based THz emitters, we demonstrate an efficient and strong THz emission from a single layer of Co2MnGa with a large anomalous Hall effect (AHE) influenced by its Weyl semimetallic nature. Strong correlations among the THz emission, AHE, and chemical ordering of the full Heusler crystal structures for Co2MnGa are shown. Based on proper structural and chemical design, the topological nature of this material facilitates systematic optimization. Our initial findings provide a new design concept for the topological influences on spin-based THz emitters, and these emitters are expected to facilitate the further development of the intriguing Weyl physics.